Influence of Artificial Sweetener on Human Blood Glucose Concentration - Ilse Skokan; P. Christian Endler; Beatrix Wulkersdorfer; Dieter Magometschnigg; Heinz Spranger (The Scientific World Journal)
Artificial sweeteners, such as saccharin or cyclamic acid are synthetically manufactured sweetenings. Known for their low energetic value they serve especially diabetic and adipose patients as sugar substitutes. It has been hypothesized that the substitution of sugar with artificial sweeteners may induce a decrease of the blood glucose. The aim of this study was to determine the reliability of this hypothesis by comparing the influence of regular table sugar and artificial sweeteners on the blood glucose concentration. In this pilot-study 16 patients were included suffering from adiposity, pre-diabetes and hypertension. In the sense of a cross-over design, three test trials were performed at intervals of several weeks. Each trial was followed by a test free interval. Within one test trial each patient consumed 150 ml test solution (water) that contained either 6 g of table sugar (“Kandisin”) with sweetener free serving as control group. Tests were performed within 1 hr after lunch to ensure conditions comparable to patients having a desert. Every participant had to determine their blood glucose concentration immediately before and 5, 15, 30 and 60 minutes after the intake of the test solution. For statistics an analysis of variance was performed. The data showed no significant changes in the blood glucose concentration. Neither the application of sugar (F4;60 = 1.645; p = .175) nor the consumption of an artificial sweetener (F2.068;31.023 = 1.551; p > .05) caused significant fluctuations in the blood sugar levels. Over a time frame of 60 minutes in the control group a significant decrease of the blood sugar concentration was found (F2.457;36.849 = 4.005; p = .020) as a physiological reaction during lunch digestion.